2021
DOI: 10.1017/s147895152100016x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of care place and diagnosis on care communication at the end of life: bereaved family members’ perspective

Abstract: Objective To investigate the influence of care place and diagnosis on care communication during the last 3 months of life for people with advanced illness, from the bereaved family members’ perspective. Method A retrospective survey design using the VOICES(SF) questionnaire with a sample of 485 bereaved family members (aged: 20−90 years old, 70% women) of people who died in hospital was employed to meet the study aim. Results Of the deceased people, 79.2% had at some po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…4,54,55 However, a study from Sweden suggested that when compared to other end-oflife care settings, those with relatives in NHs are less likely to report that their relative was treated with dignity or respect and more likely to indicate "unwanted" decisions were made during their relative's end-of-life care. 56 Taking part in care planning during a relative's end of life in RLTC also appears to enhance family members' feelings of involvement during this health transition. 57 An analysis of family involvement during a relative's final month of life in RLTC found that the majority of family members were involved with monitoring and managing their relative's care as well as helping with meals, whereas 40% provided personal care.…”
Section: Family Involvement Rltc and Key Transitionsmentioning
confidence: 99%
“…4,54,55 However, a study from Sweden suggested that when compared to other end-oflife care settings, those with relatives in NHs are less likely to report that their relative was treated with dignity or respect and more likely to indicate "unwanted" decisions were made during their relative's end-of-life care. 56 Taking part in care planning during a relative's end of life in RLTC also appears to enhance family members' feelings of involvement during this health transition. 57 An analysis of family involvement during a relative's final month of life in RLTC found that the majority of family members were involved with monitoring and managing their relative's care as well as helping with meals, whereas 40% provided personal care.…”
Section: Family Involvement Rltc and Key Transitionsmentioning
confidence: 99%
“…From the patient's point of view, aspects such as control, identity and autonomy are determining factors in safeguarding dignity (Rodríguez‐Prat et al, 2016 ). The end‐of‐life process can be seen differently with varying nuances depending on the service the patient is provided or the type of pathology they have (O'Sullivan et al, 2021 ). For example, the experience of a family caregiver could be more positive when a cancer patient is attended to in hospital, whereas for a family member of a patient who does not have cancer, they might prefer to be attended to at home (Martí‐García et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%